Haemodynamic Response Associated with Both Ictal and Interictal Epileptiform Activity Using Simultaneous Video Electroencephalography/Near Infrared Spectroscopy in a Within-Subject Study. Issue 4 (August 2015) - Monrad, Priya; Sannagowdara, Kumar; Bozarth, Xiuhua; Bhosrekar, Sugandha; Hecox, Kurt; Nwosu, Michelle; Schwabe, Michael; Meyer, Michael; Szabo, Aniko; Prigge, Jenna; Lemke, Russ; Horn, Briana; et al.
This paper reports the findings from a pilot study of four patients with medically refractory epilepsy undergoing pre-surgical evaluation with ages ranging from 5 to 17 years. Video electroencephalography recordings and data from a near infrared spectroscopy cerebral/somatic oximeter were gathered and related to electrographic seizure onset and offset as determined by a paediatric epileptologist. All four patients showed haemodynamic changes associated with epileptiform activities. The increased blood flow clearly coincided with epileptiform activity and continued to increase as the epileptiform activity built up. Regional cerebral oxygen saturation increased in the epileptogenic focus, perhaps due to loss of cerebrovascular autoregulation. These findings reinforce that near infrared spectroscopy can potentially be used in a wide spectrum of patients with epilepsy regardless of the underlying brain pathology.